DEVELOPMENT OF METHODS AND MODELS FOR THE PREVENTION OF PUMPING PHENOMENA IN A GAS TURBINE ENGINE - Kiprich, T. V.; Kharitonov, V. Н.; Dubrovin, V. I.; Pritula, A. V. (Radio Electronics, Computer Science, Control, 2024)
The aim of existing stall prevention systems in a gasturbine engine is an automatic restoration of the engine operating conditions after a surge ceasing rather than prevention of a gas-dynamic instability in turbo machines. The model of a surge prevention modulus based on the method of wavelet-analysis and Kohonen's SOM maps is suggested. A comparative analysis for stall detection results is carried out with the help of such an approach and simplified models.